ARHGAP9 siRNA inhibits gastric cancer cell proliferation and EMT via inactivating Akt, p38 signaling and inhibiting MMP2 and MMP9 - Sun, Lingjia (Int J Clin Exp Pathol, 2017)
Objective: ARHGAP9 is a RhoGTPase activating protein. This study aimed to investigate the effect of ARHGAP9 on cell proliferation of gastric cancer cell. Methods: Human gastric cancer cell line SGC7901 were transfected with ARHGAP9 siRNA and the expression of epithelial to mesenchymal transition (EMT) factors, MMPs, and activated status of Akt and p38 signaling were detected. Moreover, the migration, invasion, and viability of SGC7901 cells were determined. Results: ARHGAP9 siRNA successfully inhibited cell viability, migration and invasion. The expression of E-cadherin was significantly upregulated, and expression of Snail, Vimentin, as well as MMP2 and MMP9 were obviously downregulated. Moreover, ARHGAP9 siRNA promoted inactivation of Akt and p38 signaling by inhibiting expression of p-Akt and p-p38. Conclusion: This study showed that ARHGAP9 contributed to the viability, migration, invasion as well as EMT in gastric cancer cell line SGC7901. ARHGAP9 might be used as a therapeutic target for gastric cancer.